2020
DOI: 10.1590/2317-1782/20202019070
|View full text |Cite
|
Sign up to set email alerts
|

Postural balance in type 2 diabetics with vertigo, dizziness and/or unsteadiness

Abstract: Purpose: To evaluate the postural balance of type 2 diabetics with vertigo, dizziness, and/or unsteadiness. Methods: limit of stability, pressure center displacement area, and sway velocity of 20 patients with type 2 diabetes were compared with 22 controls using the Balance Rehabilitation Unit (BRUTM, Medicaa) posturography. Results: Compared to the control group, patients with type 2 diabetes showed a significantly lower limit of stability and a significantly higher-pressure center displacement area on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
5
1
3
Order By: Relevance
“…The difference between the T2DM and the healthy participants in static postural control are reported in previous researches. Fukunaga (24) evaluated the postural balance (limit of stability, pressure center displacement area, and sway velocity) of 20 T2DM individuals compared with 22 controls using balance posturegraphy equipment. The result found that participants with T2DM had significantly lower limits of stability, higher pressure displacement area, and higher sway velocity on a firm surface with eyes-open/eyes-closed (24), which was in line with our study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the T2DM and the healthy participants in static postural control are reported in previous researches. Fukunaga (24) evaluated the postural balance (limit of stability, pressure center displacement area, and sway velocity) of 20 T2DM individuals compared with 22 controls using balance posturegraphy equipment. The result found that participants with T2DM had significantly lower limits of stability, higher pressure displacement area, and higher sway velocity on a firm surface with eyes-open/eyes-closed (24), which was in line with our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Fukunaga (24) evaluated the postural balance (limit of stability, pressure center displacement area, and sway velocity) of 20 T2DM individuals compared with 22 controls using balance posturegraphy equipment. The result found that participants with T2DM had significantly lower limits of stability, higher pressure displacement area, and higher sway velocity on a firm surface with eyes-open/eyes-closed (24), which was in line with our study results. Similarly, another research adopting static posturography showed standing on firm surface under eyesclosed condition had a larger effect in participants with a BMI ≥30 compared to those with a BMI <30 (10).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of disability was evident among patients with T2DM who have dizziness complaint [ 16 , 17 ]. However, the issue of social participation in these patients has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Com a progressão da doença, os sintomas se tornam mais evidentes e limitantes, podendo interferir na realização das atividades de vida diária. Tremor de repouso, rigidez muscular, disfunções posturais e bradicinesia são alterações motoras ocorridas na DP [7][8][9][10] .…”
Section: Introductionunclassified
“…Com a evolução da DP a musculatura é progressivamente afetada, tornando difícil a habilidade de se movimentar com agilidade e precisão, o que altera o desempenho da escrita manual, principalmente se os sintomas acometerem o membro dominante. E entre os sintomas motores, a rigidez muscular e a bradicinesia são os mais incapacitantes para a escrita 1,8,9,11,12 .…”
Section: Introductionunclassified